Gold-catalyzed formal cyclisation/dimerization of thiophene-tethered diynes - Tšupova, Svetlana; Hansmann, Max M.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2017)
A new pathway in dual gold-catalyzed reaction of thiophene-tethered diynes has been identified. A series of fully conjugated alkynyl-substituted benzothiophenes and benzofurans was obtained by a formal cyclisation/dimerization sequence. All the products are fluorescent, owing to their extended conjugation. The mechanistic studies have been carried out, suggesting that gold acetylides take part in this transformation.
Gesehen am 28.08.2017